Diet composition of Adélie Penguins Pygoscelis adeliae at Hope/Esperanza Bay during 2014-2019 - Silvestro, Anahí Mariel (2023)
In this study, we obtained samples through stomach lavage to determine the diet of Adelie Penguins Pygoscelis adeliae during the guard and crèche periods at Hope/Esperanza Bay, Antarctica, during four breeding seasons (2014–2019, except 2016). Antarctic krill was the dominant prey, contributing > 99.6% of the diet by mass. The remainder of prey were fish, amphipods, and mollusks. Among fish, the nototheniid Pleuragramma antarcticum was the most frequent while the bathydraconid Parachaenichthys charcoti dominated by mass. Mollusks and fish increased their contribution during the crèche period in accord with seasonal patterns elsewhere.